2021
DOI: 10.1111/bcp.14851
|View full text |Cite
|
Sign up to set email alerts
|

Fatal adverse drug reactions: A worldwide perspective in the World Health Organization pharmacovigilance database

Abstract: Funding informationAgence Nationale de Sécurité du Médicament et des produits de santé Aims: Adverse drug reactions (ADRs) are important causes of death. However, the main involved drugs are relatively unknown. The present study was performed to characterise death-related drugs recorded in a large pharmacovigilance database during the last 10 years.Methods: A retrospective analysis of VigiBase, the World Health Organization pharmacovigilance database, was performed investigating fatal ADRs registered between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 26 publications
6
58
0
Order By: Relevance
“…The results of both studies indicate that DRDs are more commonly observed in male patients over 65 years old, which supports the findings of the retrospective analysis of Vigibase [31].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of both studies indicate that DRDs are more commonly observed in male patients over 65 years old, which supports the findings of the retrospective analysis of Vigibase [31].…”
Section: Discussionsupporting
confidence: 85%
“…It is interesting to point out that from both pharmacovigilance studies, the most common DRDs were hemorrhages and infections, which supports the findings in a recent retrospective analysis of VigiBase, the largest pharmacovigilance database in the world, from the World health Organization, [31] and a meta-analysis of observational studies in European hospitals [12]. Therefore, the most common involved drugs were anticoagulants and/or anti-thrombotics, and antineoplastic agents [12,31]. Preventive measures should be implemented to promote and improve closer follow-up of anticoagulant use.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, an analysis of the Swedish national pharmacovigilance database (2008–2011) shows that women and men have higher rates of nonserious and severe reactions, respectively [ 89 ]. Data from VigiBase show that fatal ADR occur more in men, in the elderly over 65 years, and in Americans [ 90 ], indicating the importance of sex–gender, age, and geographical localization. Interestingly, paradoxical ADR (which are opposite reactions to the drug’s pharmacological effects) seem to be more frequent in men than in women [ 91 ].…”
Section: Factors That Can Affect the Pharmacological Responsementioning
confidence: 99%
“…Sex and gender differences partly depend on differences in pharmacokinetics and pharmacodynamics; however, the role of the above-mentioned factors in the drug’s safety profiles is not known. However, patient adherence to a therapy or drug prescription depends on the sex and gender of patients and sex and gender of physicians, geographical localization, and microbiota [ 38 , 88 , 90 ].…”
Section: Factors That Can Affect the Pharmacological Responsementioning
confidence: 99%
“…Notably, most drugs have been excluded from the market because of their toxic effects, which have been described mainly in women ( [20] and cited literature). Women seem to be admitted to hospitals for ADR more than men ( [130], however, about this last point there are no univocal data [131,132]). Besides, women have a bigger immune response to vaccines than men [82,83], but they also have more common severe side effects [133][134][135].…”
Section: Can Male and Female Covid-19 Patients Have The Same Safety Profile As Covid-19 Free Patients?mentioning
confidence: 99%